Pemberdayaan Ekonomi Masyarakat Miskin Berbasis UPKU Panca Usaha di Desa Mojoruntut Kecamatan Krembung - Prihatin, Sekar Novi; Fauziah, Luluk (Universitas Muhammadiyah Sidoarjo, 2013)
This study is aimed to determine the role of finance and business management unit (UPKu) Panca Usaha and inhibiting and supporting factors the unit in the economic empowerment of the poor in Mojoruntut Village, Krembung Sub-district, Sidoarjo. The method used a qualitative research and the technique of collecting data through observation, interview as well as documentation. The results showed that the role of UPKu in economic empowerment of the poor is seen through the realization of Productive Economic Business Savings and Loan (UEP-SP), which provides easy, inexpensive and quick capital services to pioneer or develop a business for poor households and create Business activities of Real Sector (USR). The supporting factors included the support of provincial and district government, community participation, and the guidelines of Standard Operating Program (SOP) and Standard Service Program (SPP). While inhibiting factor were the lack of knowledge and Human Resources (HR) owned by poor households in managing a business, a consumer culture, and the low level of public awareness.